The Effect Of Compensation and Talent Management On Employee Performance (Survey of Permanent Employees in the Production Department of PT. Rentang Buana Niagamakmur Tasikmalaya) - Islamiyah, Putri Andini; Sutrisna, Arga; Arif, Arif (Universitas Dehasen Bengkulu, 2024)
This research was conducted with the aim of determining the influence of Compensation and Talent Management on Employee Performance (Survey of Permanent Employees in the Production Department of PT. Rentang Buana Niagamakmur Tasikmalaya). The method used in this research is a survey method with a quantitative approach, using data obtained directly through questionnaires distributed to 38 respondents who are permanent employees of the Production Department of PT. Range Buana Niagamakmur Tasikmalaya. The technique used in this research is multiple linear regression analysis. Based on the research results, it can be seen that Compensation and Talent Management simultaneously have a significant effect on the Performance of Permanent Employees in the Production Department of PT. Rentang Buana Niagamakmur Tasikmalaya. Compensation partially has a significant effect on the Performance of Permanent Employees in the Production Department of PT.Rentang Buana Niagamakmur Tasikmalaya, and Talent Management partially has a significant effect on the Performance of Permanent Employees in the Production Department of PT.Rentang Buana Niagamakmur Tasikmalaya.